THE COMMODIFICATION OF CULTURE IN BALI IN THE FRAME OF CULTURAL TOURISM - INDRIANTO, AGOES TINUS (ASEAN Journal on Hospitality and Tourism, 2005)
As one of the international tourist destinations in the world, Bali has been the landmark of tourism in Indonesia. Supported by excellent tourist facilities and infrastructure, Bali has become a very touristic place. This condition forces the Balinese to adapt with the new environment that may influence their daily life. The cultural richness of Bali has been the main focus of the Government to boost and maintain Bali as one of the world’s top destinations.This has made the Balinese and its culture undergo modification in terms of performances, values and the way of life. This paper aims to identify the commodification of culture in Bali which is the result of the development of cultural tourism in Bali. Furthermore this paper reveals the cultural commodification from the perspectives of the tourists, the Balinese and the Government. The paper also discusses the social problems occur in Bali, the efforts to restore Balinese culture and the future of cultural tourism in Bali.